Excellent dielectric constants observed in heterogeneous conduction Ba(Zr0.25Ti0.75)O3ceramics doped with Sr(Fe0.5Nb0.5)O3 - Pharatree Jaita (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. The (1-x)Ba(Zr0.25Ti0.75)O3-xSr(Fe0.5Nb0.5)O3or (1-x)BZT-xSFN ceramics have been fabricated via a solid-state reaction technique. All ceramics exhibit a pure phase perovskite with cubic symmetry. The addition of a small amount of SFN (x = 0.1) produces an obvious change in dielectric behavior. Very high dielectric constants (εr> 164,000 at 1 kHz and temperature > 150°C) are observed and the value is obviously higher than dielectric constants for Ba(Zr0.25Ti0.75)O3and Sr(Fe0.5Nb0.5)O3ceramics. The ferroelectric measurement data suggests that the unmodified sample exhibited a ferroelectric behavior. However, a transformation from a ferroelectric to a relaxor-like behavior is noted with increasing x concentration. Impedance Spectroscopy (IS) analysis indicates that the presence of excellent dielectric constants is due to the heterogeneous conduction in the ceramics after adding SFN, which can be explained in terms of the Maxwell-Wagner polarization mechanism.